MODERN DIRECTIONS OF ECO-DESIGN IN THE FASHION INDUSTRY - Pashkevych, K. L.; Khurana, K.; Kolosnichenko, O. V.; Krotova, T. F.; Veklich, A. M. (Art and Design, 2020)
Determination of directions of eco-design used for designing of the products of the fashion industry, their formulation, and characteristics. Literary-analytical and visual-analytical methods, as well as system-structural analysis, are used. The activities and the products of modern brands of clothes and accessories in eco-style have been analyzed; the trends of ecological direction in the fashion industry and the latest developments in the field of production of eco-friendly textile have been researched. The directions of eco-design, which exist in the modern fashion industry, have been highlighted, in particular: clothes made from eco-materials; upcycling, trashion, zero waste cutting, creation of the clothes that have an extended period of moral agelessness. Each of the directions has been provided with a description of its features and the examples of its practical use in the modern fashion industry have been presented. Scientific novelty consists in determination, description and systematization of directions of eco-design, according to which the eco-products are designed; it also consists in outlining of tendencies in their modern practical use. The considered directions of eco-design can be used for the modern practice of designing and production of clothes and accessories, in the educational process devoted to modern directions in design, ecological tendencies in design of the clothes.